2014
DOI: 10.1590/0074-0276140228
|View full text |Cite|
|
Sign up to set email alerts
|

Malaria in Brazil: what happens outside the Amazonian endemic region

Abstract: Brazil, a country of continental proportions, presents three profiles of malaria transmission. The first and most important numerically, occurs inside the Amazon. The Amazon accounts for approximately 60% of the nation’s territory and approximately 13% of the Brazilian population. This region hosts 99.5% of the nation’s malaria cases, which are predominantly caused by Plasmodium vivax (i.e., 82% of cases in 2013). The second involves imported malaria, which corresponds to malaria cases acquired outside the reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
172
0
24

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(206 citation statements)
references
References 81 publications
(119 reference statements)
6
172
0
24
Order By: Relevance
“…Beyond its importance as a vector of P. vivax to humans, it is related to transmission of Plasmodium simium among monkeys and/or humans (Pina-Costa et al 2014). Recently, Brasil et al (2017) suggested that transmission of P. simium to humans may have been neglected because it seems more important than previously thought.…”
Section: Biology Of Malaria Vectors and The Transmission Of Parasitesmentioning
confidence: 99%
“…Beyond its importance as a vector of P. vivax to humans, it is related to transmission of Plasmodium simium among monkeys and/or humans (Pina-Costa et al 2014). Recently, Brasil et al (2017) suggested that transmission of P. simium to humans may have been neglected because it seems more important than previously thought.…”
Section: Biology Of Malaria Vectors and The Transmission Of Parasitesmentioning
confidence: 99%
“…Northern Brazil is an endemic malaria region (Barata 1995, Oliveira-Ferreira et al 2010) and a growing number of researches make use of the Brazilian epidemiological surveillance system of malaria (SIVEP-Malaria) database. Costa et al 2014). The Malaria's Epidemiological Surveillance System (SIVEP-Malaria) is the main tool used by PNCM to improve the production of information about malaria.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, these numbers are decreasing and the amount of cases of the disease recorded in recent years went down: 267 047 cases in 2011, 242,756 in 2012 (a reduction of 9.1%) and 178,613 in 2013 (down 26.4%). The predominant geographical location of cases is in Legal Amazonia (99.5%), with preponderance in the states of Acre, Amazonas, Pará and Rondônia (PINA-COSTA et al, 2014).…”
Section: Introductionmentioning
confidence: 99%